International labor mobility and knowledge flow externalities - Oettl, Alexander; Agrawal, Ajay (Journal of International Business Studies, 2008)
Although knowledge flows create value, the market often does not price them accordingly. We examine “unintended” knowledge flows that result from the cross-border movement of inventors (i.e., flows that result from the move, but do not go to the hiring firm). We find that the inventor's new country gains from her arrival above and beyond the knowledge flow benefits enjoyed by the firm that recruited her (National Learning by Immigration). Furthermore, the firm that lost the inventor also gains by receiving increased knowledge flows from that individual's new country and firm (Firm Learning from the Diaspora). Surprisingly, the latter effect is only twice as strong when the mover moves within the same multinational firm, suggesting that knowledge flows between inventors do not necessarily follow organizational boundaries, thus creating opportunities for public policy and firm strategy.